First records for Cissia themis (Lepidoptera: Nymphalidae) from Colombia and Venezuela - NAKAHARA, SHINICHI; MARÍN, MARIO A.; MITSUHASHI, WATARU (Revista Colombiana de Entomología, 2012)
A new country record for Cissia themis from Colombia and Venezuela is reported here. This record is also the first report for South America except for the island of Trinidad. Specimens of C. themis are often misidentified and found mixed in with its congener C. similis in public collections and so the morphology of C. themis is compared to its congener, C. similis.